Comprehensive clinical analysis of patients with primary malignant tumor of pituitary gland: A population-based study - Sun, Xu; Huo, Lanqing; Wang, Xin; Zhang, Chunlan; Zhao, Ailin (Frontiers in Surgery, 2022)
Abstract Background and Objectives: This study aims to perform a comprehensive clinical analysis of patients with primary malignant pituitary tumors (PMPT) that involves incidence, demographics, treatments, long-term survival and death causes. Materials and methods: Patients with PMPT were identified from registries of the Surveillance, Epidemiology, and End Results (SEER) database. Frequencies and average annual age-adjusted rate (AAR) were calculated for incidence trend analyses using Join-point regression. Uni- and multi-variate Cox regression were conducted to identify potential prognostic factors associated with patients’ survival outcome. Using Kaplan-Meier method and log-rank test, survival curves were plotted and compared, respectively. Propensity score matching (PSM) was performed to balance baseline characteristics. Results: The AAR for PMPT was 0.233 (95%CI: 0.205-0.264) per 1,000,000 using 9 SEER registries from 1975 to 2017. The incidence trend has declined over years but without significance (-1.04% per year, P=0.10). Besides, an older age may indicate higher incidence rate for both pediatric and adult patients. From 18 SEER registries, a total of 501 PMPT patients were also identified. Uni- and multivariate Cox regression showed age, sex, tumor extent and marital status were independent prognostic factors for malignant pituitary tumor. Via PSM, we found that patients who received surgery, radiotherapy and chemotherapy did not demonstrate significantly different survival than those who did not. Conclusion: This study firstly conducts a comprehensive clinical analysis of patients with PMPT and provides guide effects on future study designs. More studies should be conducted to focus on its characteristics and therapy.